The impact of electronic currency trading on reality of fiat currencies "The Iraqi financial market as a model - Assistant teacher Aeshah Mohammed A.Sattar; Assistant Prof. Dr. Adel Mansour Fadel (مجلة الدراسات الاقتصادية والادارية)
It contributed to the research into the digital currency market on the volume of digital currency trading, as electronic currency trading in Iraq developed from modern operations, which contributed to the transformation into the field of Iraqi financial transactions, as Iraqi finances witnessed an electronic transformation to (70%), and this contributes globally to The clear development, in addition to the ease of transactions and currency transfers between individuals, due to, and sometimes two-by-two, financial transactions, where the descriptive model was used to explain the trading of electronic currencies, and the research reached results, the most important of which are: the presence of an inevitable visible reduction in dealing and handling of banknotes well, and replacing them with electronic money.